iTRAQ-Based Quantitative Proteomic Analysis Reveals Toxicity Mechanisms in Chlamys farreri Exposed to Okadaic Acid - Wang, Xin; Wang, Dan; Zhang, Tianyu; Zhang, Qianqian; Zhao, Jianmin (Frontiers in Marine Science, 2021)
Okadaic acid (OA), produced by dinoflagellates during harmful algal blooms, is a principal diarrhetic shellfish poisoning toxin. This toxin poses a potential threat to bivalves with economic values. To better understand the toxicity mechanism of OA to bivalves, in this study, oxidative stress biomarkers (superoxide dismutase, SOD; catalase, CAT; glutathione S-transferase, GST; malondialdehyde, MDA) and the expression of detoxification genes (heat shock protein 70, HSP70; heat shock protein 90, HSP90; cytochrome P450, CYP450) were assessed in the gills of scallops Chlamys farreri after 24 h, 48 h and 96 h exposure to OA. In addition, the digestive glands of scallops exposed to OA for 96 h were dissected for an iTRAQ based quantitative proteomic analysis. The results of OA exposure experiments showed that OA induces oxidative stress and significant enhancement of the expression of detoxification genes in scallops. The proteomics analysis revealed that 159 proteins altered remarkably in OA-treated scallops, and these proteins were involved in phagosomes, regulation of actin cytoskeleton, adherens junction, tight junction, and focal adhesion. Amino acid biosynthesis, carbon metabolism, pentose phosphate pathway, fructose and mannose metabolism in the digestive glands were also significantly impacted. Our data shed new insights on the molecular responses and toxicity mechanisms of C. farreri to OA.